An HIV Preexposure Prophylaxis Demonstration Project and Safety Study for Young MSM. (1st January 2017) - Hosek, Sybil G.; Rudy, Bret; Landovitz, Raphael; Kapogiannis, Bill; Siberry, George; Rutledge, Brandy; Liu, Nancy; Brothers, Jennifer; Mulligan, Kathleen; Zimet, Gregory; Lally, Michelle; Mayer, Kenneth H.; et al.
Abstract : Background: Young men who have sex with men (YMSM) are a key population for implementation of preexposure prophylaxis (PrEP) interventions. This open-label study examined adherence to PrEP and assessed sexual behavior among a diverse sample of YMSM in 12 US cities. Methods: Eligible participants were 18- to 22-year-old HIV-uninfected MSM who reported HIV transmission risk behavior in the previous 6 months. Participants were provided daily tenofovir disoproxil fumarate/emtricitabine (Truvada). Study visits occurred at baseline, monthly through week 12, and then quarterly through week 48. Dried blood spots were serially collected for the quantification of tenofovir diphosphate (TFV-DP). Results: Between March and September 2013, 2186 individuals were approached and 400 were found to be preliminarily eligible. Of those 400, 277 were scheduled for an in-person screening visit and 200 were enrolled (mean age = 20.2; 54.5% black, 26.5% Latino). Diagnosis of sexually transmitted infections, including urethral and rectal chlamydial/gonococcal infection and syphilis, at baseline was 22% and remained high across visits. At week 4, 56% of participants had TFV-DP levels consistent with ≥4 pills per week. By week 48, 34% of participants had TFV-DP levels consistent with ≥4 pills per week, with a noticeable drop-off occurring at week 24. Four HIV seroconversions occurred on study (3.29/100 person-years). Condomless sex was reported by >80% of participants, and condomless anal sex with last partner was associated with higher TFV-DP levels. Conclusions: Acceptability of PrEP was high, and most participants achieved protective drug levels during monthly visits. As visit frequency decreased, so did adherence. YMSM in the United States may need PrEP access in youth-friendly settings with tailored adherence support and potentially augmented visit schedules.